Business modeling and data mining - Pyle, Dorian (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2003)
Business Modeling and Data Mining demonstrates how real world business problems can be formulated so that data mining can answer them. The concepts and techniques presented in this book are the essential building blocks in understanding what models are and how they can be used practically to reveal hidden assumptions and needs, determine problems, discover data, determine costs, and explore the whole domain of the problem. This book articulately explains how to understand both the strategic and tactical aspects of any business problem, identify where the key leverage points are and determine where quantitative techniques of analysis -- such as data mining -- can yield most benefit. It addresses techniques for discovering how to turn colloquial expression and vague descriptions of a business problem first into qualitative models and then into well-defined quantitative models (using data mining) that can then be used to find a solution. The book completes the process by illustrating how these findings from data mining can be turned into strategic or tactical implementations. Teaches how to discover, construct and refine models that are useful in business situations Teaches how to design, discover and develop the data necessary for mining Provides a practical approach to mining data for all business situations Provides a comprehensive, easy-to-use, fully interactive methodology for building models and mining data Provides pointers to supplemental online resources, including a downloadable version of the methodology and software tools.
The world, knowledge, and models -- Translating experience -- Modeling and mining : putting it together -- Framing business models -- Getting the right model -- Getting the model right -- Deploying the model -- Getting started -- What mining tools do -- Getting the initial model : basic practices of data mining -- Improving the model -- Deploying the mined model -- Methodology.
Includes bibliographical references (p. 665-671) and index.
Keywords: Business -- Data processing -- Management; Data mining; Database management; Information resources management; Management information systems; Business -- Data processing -- Management. Data mining. Database management. Information resources management. Management information systems; Electronic books